The Role of Nutritional Interventions in Diabetes Management (International Journal of Food and Nutritional Sciences, 2021)
Insulin resistance and partial or total insulin secretion deficit cause hyperglycemia in diabetes mellitus. Polydipsia, polyuria, impaired eyesight, poor wound healing, and nerve damage are common. As a metabolic and endocrine condition, diabetes affects glucose, lipid, and protein metabolism. Thus, dietary therapy is essential for diabetes management. The recommended daily calorie intake is 50%–55% carbs, preferably low-glycemic index. To diversify diabetes diets, nonnutritive sweeteners are recommended. Protein requirements are 15-20% of total caloric consumption, similar to the overall population. General recommendations (20–35 g) include soluble and insoluble fibers, which prolong gastric emptying, avoid constipation, lower serum cholesterol, and lower blood glucose response. Diabetics should eat low-fat to maintain a healthy weight. Fats should make up 30% of daily calories, with less than 10% saturated, polyunsaturated, and monounsaturated. Diabetics don't need vitamin and mineral supplements if they eat well. Despite substantial study on nutritional aspects in diabetes causation and therapy, specific nutrient risks are unknown. Government regulations and legislation, together with individual and community-based programs, are needed to maximize dietary interventions in diabetes treatment.